Pendampingan Kesehatan Fisik, Mental, Dan Sosial Dalam Masa New Normal Terhadap Anak Binaan Panti Asuhan As-Salaam Kota Pekanbaru - Tyagita Widya Sari; Ratih Ayuningtiyas; Uly Astuti Siregar; Imelda Fitri; Nurul Aiyuda (LPMP Imperium, 2022)
This activity aims to assist and increase the knowledge of the children fostered by the orphanage in achieving a state of complete physical, mental and social well-being, which is not limited to being free from disease or disability, especially during the new normal period related to the Covid-19 pandemic. The method used in this activity is in the form of health education using slide presentation tools. Participants were given material on physical, mental, and social health, as well as Covid-19 prevention behavior and continued with a question and answer session, where there was a knowledge questionnaire filled out before and after health education. The participants of the activity were 10 children fostered by the orphanage where the activity lasted for 90 minutes. Health assistance efforts are sufficient in achieving goals, as indicated by changes in the results of the pretest and posttest questionnaires, but improvements need to be made to further service activities, by combining health counseling methods with other relevant service methods.